2001
DOI: 10.1107/s0907444901002530
|View full text |Cite
|
Sign up to set email alerts
|

X-ray structure of bovine pancreatic phospholipase A2at atomic resolution

Abstract: Using synchrotron radiation and a CCD camera, X-ray data have been collected from wild-type bovine pancreatic phospholipase A(2) at 100 K to 0.97 A resolution allowing full anisotropic refinement. The final model has a conventional R factor of 9.44% for all reflections, with a mean standard uncertainty for the positional parameters of 0.031 A as calculated from inversion of the full positional least-squares matrix. At 0.97 A resolution, bovine pancreatic phospholipase A(2) reveals for the first time that its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 36 publications
8
47
1
1
Order By: Relevance
“…(i) X-ray structures of several sPLA 2 -inhibitor complexes do not reveal imidazole ring flipping. 16 36 which is too far apart for a H-bond. Thus, the N d1 atom of H48 likely forms a hydrogen bond only with the transition-state analog.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(i) X-ray structures of several sPLA 2 -inhibitor complexes do not reveal imidazole ring flipping. 16 36 which is too far apart for a H-bond. Thus, the N d1 atom of H48 likely forms a hydrogen bond only with the transition-state analog.…”
Section: Discussionmentioning
confidence: 99%
“…Both NMR studies 20 and the recent 0.97 Å ultrahigh resolution crystal structure 36 of free bovine pancreatic sPLA 2 show that H48 and D99 form a H-bond involving the N 12 of the imidazole ring. Taken together, we conclude that the LBHB is formed between H48 and the inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The presumed IBS residues [51] of AtxA, surrounding the opening to the active-site pocket with His 48 , are shaded dark grey and pointed towards the reader. The residues identified so far by site-directed mutagenesis as being important for neurotoxicity of AtxA are indicated, and are shown in black.…”
Section: Figure 3 Location Of the Residues Important For Neurotoxicitmentioning
confidence: 99%
“…Considering that ARM-and HEAT-like motifs are commonly found to mediate protein-protein interactions by their modular recognition of extended peptide regions (34), it is reasonable to speculate that the N-terminal domain of Tse3 is crucial for the proper folding and conformational stabilities of the Tse3. Although some enzymes that catalyze a hydrolytic reaction, such as phospholipase A2 and staphylococcal nuclease, bind with Ca 2ϩ in their active site as a catalytic factor (40,41), Ca 2ϩ binding and involvement of enzymatic activity are not observed in the reported T6SS toxins (15, 16, 18 -22) or the goose-type lysozyme homologues (35)(36)(37). Based on the high-resolution structure and biochemical studies presented here, we identified three Ca 2ϩ ions that bind with Tse3; two Ca 2ϩ ions bind directly in the catalytic site and adjacent to the catalytic residue Glu-250 (Figs.…”
Section: Discussionmentioning
confidence: 99%